Affirmative action and university fit: Evidence from proposition 209 - Peter Arcidiacono; Esteban Aucejo; Patrick Coate; V. Joseph Hotz (Institute for the Study of Labor (IZA), 2012)
Proposition 209 banned using racial preferences in admissions at California's public colleges. We analyze unique data for all applicants and enrollees within the University of California (UC) system before and after Prop 209. After Prop 209, graduation rates of minorities increased by 4.4%. We characterize conditions required for better matching of students to campuses to account for this increase. We find that Prop 209 did improve matching and this improvement was important for the graduation gains experienced by less-prepared students. At the same time, better matching only explains about 20% of the overall graduation rate increase. Changes after Prop 209 in the selectivity of enrolled students explains 34-50% of the increase. Finally, it appears UC campuses responded to Prop 209 by doing more to help retain and graduate its students, which explains between 30-46% of the post-Prop 209 improvement in the graduation rate of minorities.
Keywords: I23; J15; 330; affirmative action; college enrollment; college graduation; mismatch; Ethnische Diskriminierung; Gleichbehandlungsrecht; Hochschule; Schulbesuch; Bildungsabschluss; Kalifornien